Electronic structure of AlCrN films investigated using various photoelectron spectroscopies and ab initio calculations. (12th January 2017) - Tatemizo, N; Imada, S; Miura, Y; Yamane, H; Tanaka, K
Abstract: The valence band (VB) structures of wurtzite AlCrN (Cr concentration: 0–17.1%), which show optical absorption in the ultraviolet-visible-infrared light region, were investigated via photoelectron yield spectroscopy (PYS), x-ray/ultraviolet photoelectron spectroscopy (XPS/UPS), and ab initio density of states (DOS) calculations. An obvious photoelectron emission threshold was observed ~5.3 eV from the vacuum level for AlCrN, whereas no emission was observed for AlN in the PYS spectra. Comparisons of XPS and UPS VB spectra and the calculated DOS imply that Cr 3 d states are formed both at the top of the VB and in the AlN gap. These data suggest that Cr doping could be a viable option to produce new materials with relevant energy band structures for solar photoelectric conversion.